2019
DOI: 10.1097/meg.0000000000001414
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clostridium difficile infection among hospitalized inflammatory bowel disease patients in Greece

Abstract: Background Inflammatory bowel disease (IBD) is an independent risk factor for Clostridium difficile infection (CDI), which is associated significantly with disease severity. We aimed to determine the rates of CDI among hospitalized IBD patients in major tertiary referral hospitals in Greece. Patients and methods A retrospective analysis was carried out of stool cultures from hospitalized patients investigated for diarrhea, during 2016, tested for CDI wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A study reported that the prevalence of CDI in IBD patients receiving azathioprine was significantly higher, and that patients on combined-therapy with a biologic agent and an immunomodulator showed no CDI. 16 Similarly, another study demonstrated that the use of immunomodulators such as azathioprine and 6-mercaptopurine, or mesalamine, was associated with the development of CDI. The maintenance of immunosuppression was independently associated with the emergence of CDI in IBD patients.…”
Section: Pathogenesismentioning
confidence: 97%
“…A study reported that the prevalence of CDI in IBD patients receiving azathioprine was significantly higher, and that patients on combined-therapy with a biologic agent and an immunomodulator showed no CDI. 16 Similarly, another study demonstrated that the use of immunomodulators such as azathioprine and 6-mercaptopurine, or mesalamine, was associated with the development of CDI. The maintenance of immunosuppression was independently associated with the emergence of CDI in IBD patients.…”
Section: Pathogenesismentioning
confidence: 97%
“…A retrospective analysis in Greece showed that compared with patients without IBD, hospitalized IBD had a higher CDI rate. 19 We found that CD patients in group A2 were more likely to have CDI than group A3, the occurrence rates were 17.05% and 6.67%, respectively. CDI could increase the health care burden and 90-day CDI-specific readmission rate of IBD, 20 and it could increase the risk of surgery by depleting the beneficial fecal microbiome and methionine biosynthesis.…”
Section: Discussionmentioning
confidence: 66%
“…When being asked to comment on CDI management in IBD, 46% of 169 gastroenterologists (25% of respondents were IBD specialists) opted for a combination of immunosuppression and antibiotics, while the remaining 54% preferred antibiotics alone to treat the flare. 32,44 In addition, Beniwal-Patel et al suggested that new immunosuppressants should not be started and scheduled infusions should be suspended until the symptoms of C. difficile are resolved in the case of new CDI. 10 While Krishna et al pointed out that IBD patients with CDI should be treated with appropriate antibiotics immediately.…”
Section: How To Manage Medications For Ibdmentioning
confidence: 99%